Impact of Effective Microorganisms (EM) Application on the Physical Condition of Haplic Luvisol - Jacek Pranagal; Sławomir Ligęza; Halina Smal (Agronomy, 2020)
The study set out to determine changes in the soil air-water properties, the water-stable aggregate share and organic carbon content as effects of a five-year application of effective microorganisms (EM-A). The hypothesis that long-term applied EM-A biopreparations have a positive effect on the soil physical condition has not been confirmed. Haplic Luvisols originating from silt were studied in a field experiment after EM-A biopreparation treatment. The soil samples with the natural structure preserved intact were collected three times each year. The properties of the soil determined in the study were: particle density, total organic carbon content, bulk density, total porosity, air capacity, air permeability, soil moisture at sampling, field water capacity, available water content, unavailable water content, and water-stable aggregate content. The ratio of field water capacity and total porosity (FC/TP) was calculated. It was found that EM-A application primarily leads to a decrease in the content of organic carbon and water-stable aggregates. This was an adverse effect. Total organic carbon (TOC) and water-stable aggregates proved to be very sensitive indicators for assessing the soil physical condition. However, changes in soil compaction and air–water properties did not show significant deterioration. Our research addresses the data gaps about EM application to soil.